The Influence of the Self-Assessment System on Accountability and Tax Transparency of Swiftlet Nests in Gorontalo Regency - Maya Apriyani Maalumu; Felmi D. Lantowa; Fitria Melynsyah Yusuf (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The implementation of the Self-Assessment System has become an essential strategy for improving accountability and transparency in local tax administration, particularly for swiftlet nest taxes that contribute to regional revenue. Despite the significant economic potential of the swiftlet nest industry in Gorontalo Regency, tax realization remains relatively low due to limited taxpayer compliance, inadequate understanding of tax obligations, and weaknesses in tax administration. This quantitative study employed an explanatory research design involving 45 respondents selected through purposive sampling from registered swiftlet nest taxpayers and officials of the Regional Revenue Agency. Data were collected using structured questionnaires and analyzed through descriptive statistics, validity and reliability tests, classical assumption tests, and simple linear regression with IBM SPSS Statistics 25. The findings demonstrate that the Self-Assessment System exerts a positive and statistically significant influence on both accountability and transparency in swiftlet nest tax management. The system explains 67.1% of the variation in accountability and 42.1% of the variation in transparency, indicating that improved taxpayer participation in calculating, reporting, and paying taxes independently strengthens responsible tax administration and enhances information openness. These findings provide empirical evidence that optimizing the implementation of the Self-Assessment System through continuous taxpayer education, effective supervision, and improved administrative services can strengthen local tax governance and support the optimization of regional own-source revenue. The study contributes to the limited empirical literature concerning accountability and transparency within the administration of local taxes in Indonesia.